ASUPAN ZAT BESI, ASAM FOLAT, DAN SENG TERHADAP KADAR HEMOGLOBIN PADA IBU HAMIL DI PUSKESMAS PACCERAKKANG KECAMATAN BIRINGAKANAYA KOTA - Abdullah Tamrin (Jurusan Gizi Poltekkes Kemenkes Makassar, 2019)
ABSTRACTAnemia is a health problem that is often found in developing countries including indonesia. Iron deficiency anemia often occurs in pregnant women. Other micronutrient deficiencies such as folic and zinc and copper also play a role in the occurrence of anemia in pregnancy. The purpose of the study was to determine the relationship of iron determine the relationship of iron, folid acid, and zinc intake to hemoglobin levels in pregnant women in Paccerakkang health center Biringkanaya district Makassar city. This type of research was observational with a cross sectional stud design. The sample in this study were pregnant women who had normal hemoglobin levels of 15 people and abnormal hemoglobin levels of 17 people who examined at Paccerakkang health center Biringkanaya district, Makassar city. Iron intake, folid acid and zinc were obtained by using the 24 hour recall method and the respondents identity data was obtained from direct interviews using a questionnaire while the hemoglobin data was obtained through hemoglobin examination at Paccerakkang health center Biringkanaya district, Makassar city. The results of the analysis between the relationship between iron intake and hemoglobin levels with p value = 0,010 which means there is a relationship between iron and hemoglobin level. The results of the analysis between the relationship of folic acid intake with hemoglobin levels with p value=0,020 which means there is a relationship between folid acid intake and hemoglobin level. The results of the analysis between the relationship between zinc intake and hemoglobin level were p=0,015 which means that there is a relationship between zinc intake and hemoglobin level